Renewable power and energy : photovoltaic systems. - Price, Gary D. (Electrical power collection., 2018)
Photovoltaic power systems are becoming a significant source of energy in our energy resource mix today. It is essential these systems are reliable, safe and secure. Precise engineering design is required to insure these new power systems meet these requirements. In particular, interconnected systems with existing utility power systems must operate in synchronism and improve overall quality of the electrical power grid. This textbook is intended to identify and explain engineering procedures for the design and operation of photovoltaic systems. The first chapters include a review of conventional electrical power systems as implemented in the United States and common to all electrical systems throughout the world. Other types of renewable energy systems are also introduced. The heart of the textbook is focused on the design of interconnected and stand-alone PV systems. Battery storage is becoming an integral part of PV systems, and a significant portion of the textbook is dedicated to energy storage for stand-alone and back-up power systems. Economics and structural considerations are included as an essential part of the engineering design process.